2018
DOI: 10.4186/ej.2018.22.1.257
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater and River Interaction Parameter Estimation in Saigon River, Vietnam

Abstract: Abstract. The Saigon River system is one of the largest resources contributing water supply for domestic and industrial fields in the Ho Chi Minh City and Binh Duong Province where the drought issue is occurring at downstream area in recent years [1]. To manage the water resources in Saigon Basin effectively, the groundwater and river interaction parameter needs to be assessed systematically. However, in the past researches, the parameters seem to be less described with full understandings. In this study, a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…However, Van and Koontanakulvong (2018) leading some counter-effects on the net discharge (see Appendix Appendix A.3). Interestingly, these fluctuations are not correlated to precipitations and could partially explain the deficit in net water discharge compared to precipitation.…”
Section: Residual Dischargementioning
confidence: 99%
“…However, Van and Koontanakulvong (2018) leading some counter-effects on the net discharge (see Appendix Appendix A.3). Interestingly, these fluctuations are not correlated to precipitations and could partially explain the deficit in net water discharge compared to precipitation.…”
Section: Residual Dischargementioning
confidence: 99%
“…Indeed, according to Oehler et al (2019), DSi concentration in the water column can be particularly elevated during the ebb tide by the contribution of DSi in groundwater which is greater than in surface water. Further, results of interaction analysis between groundwater and river showed that Saigon River indeed received water from groundwater at upstream and contributed to groundwater at downstream (Pham and Koontanakulvong, 2018).…”
Section: Aerobic Degradation Of Organic Carbon (Aerobic Respiration)mentioning
confidence: 93%
“…The water levels were simulated by using the surface water model [14] to input by river and canal nodes in the groundwater flow modelling. Additionally, the limited river conductance from previous model [15] was interpolated to other river and canal sections by the function of interaction parameter and ratio of wetted parameter [16] to simulate the river leakage of the first aquifer. From upper estimation, initial groundwater abstraction of each district and aquifer was by year and seasonal from 2007 to 2016.…”
Section: Groundwater Modelling Processmentioning
confidence: 99%